2016
DOI: 10.1902/jop.2016.150612
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory and Osteoprotective Effects of Cannabinoid‐2 Receptor Agonist HU‐308 in a Rat Model of Lipopolysaccharide‐Induced Periodontitis

Abstract: This study demonstrates anti-inflammatory, osteoprotective, and prohomeostatic effects of HU-308 in oral tissues of rats with LPS-induced periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 50 publications
(109 reference statements)
4
62
0
6
Order By: Relevance
“…Additionally, cannabidiol has been involved in the promotion of mesenchymal cells migration and osteoblastic differentiation through the activation of CB2r and the inhibition of GPR55, while AM630 abolished the effects of cannabidiol . Overall, these results are consistent with our previous studies, where stimulation of CB1r and CB2r with meth‐AEA and HU308, respectively, produced a marked reduction in the inflammatory mediators in gingival tissue and ABL . According to the current study, the blockage of specific cannabinoid receptors avoids the binding of endogenous ligands which are increased under inflammatory conditions, and the activation of subsequent intracellular pathways.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, cannabidiol has been involved in the promotion of mesenchymal cells migration and osteoblastic differentiation through the activation of CB2r and the inhibition of GPR55, while AM630 abolished the effects of cannabidiol . Overall, these results are consistent with our previous studies, where stimulation of CB1r and CB2r with meth‐AEA and HU308, respectively, produced a marked reduction in the inflammatory mediators in gingival tissue and ABL . According to the current study, the blockage of specific cannabinoid receptors avoids the binding of endogenous ligands which are increased under inflammatory conditions, and the activation of subsequent intracellular pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Although the effects of the activation of the ECS are complex and remain subjected to continuous research, many in vivo and in vitro studies have demonstrated that the stimulation of CB1r as well as CB2r reduces the level of inflammatory mediators and bone resorption in animal tissues . ‒ In previous studies of our group, inflammation in gums and ABL have been prevented by the CB1r and CB2r separate activation, but there is no record of the complete blockage of specific cannabinoid receptors.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…iNOS‐derived NO can lead to the destruction of collagen fibers via up‐regulated matrix metalloproteinases and apical migration of the junctional epithelium . It has been reported that the level of iNOS is higher in gingiva with periodontitis is higher than in healthy gingiva . Also, iNOS levels increase with severe inflammation in periodontal tissues .…”
Section: Discussionmentioning
confidence: 99%